Electromagnetic wave forward modeling of coal-gangue mixed model in top coal caving mining face. (December 2022) - Si, Lei; Xing, Feng; Wang, Zhongbin; Tan, Chao
The automatic control of top coal caving is of great significance to realize intelligent coal mining. In the process of top coal caving, a coal-gangue mixed area containing coal, gangue, and air is formed at the tail beam of the hydraulic support, which has different electromagnetic parameters, different volumes, and different shapes. To explore the transmission characteristics of electromagnetic wave in coal-gangue mixed model and the influence of different gangue ratios on electromagnetic wave propagation, the coal-gangue mixed model is established based on the random medium theory. Some electromagnetic forward modeling is carried out with different coal-gangue granularities, electromagnetic parameters, and gangue ratios based on finite-difference time-domain (FDTD) and finite-integration time-domain (FITD) methods. The results show that different granularities of coal and gangue will affect the amplitude of electromagnetic wave time-domain waveform. Under the same particle size, the equivalent electromagnetic parameters in the coal-gangue mixed medium will be larger with higher gangue ratio. Furthermore, the difference of transmitted wave signals between different gangue ratios will be larger with higher electromagnetic parameters difference of the coal and gangue. For higher refractive index, the propagation velocity of electromagnetic wave in the medium and the transmitted wave amplitude will be smaller. In addition, the comparison results illustrate that the rules of electromagnetic wave propagation obtained by FDTD and FITD methods are basically the same, which verifies the correctness of the simulations in this paper. The simulation results can lay a theoretical foundation for identifying the coal-gangue mixed degree in the process of top coal caving.